Climate and health capacity building for health professionals in the Caribbean: A pilot course - Sorensen, Cecilia; Hamacher, Nicola; Campbell, Haley; Henry, Paula; Peart, Keriann; De Freitas, Loren; Hospedales, James (Frontiers in Public Health, 2023)
Climate change is a reality in the Caribbean and its effects are already harming health, yet the health workforce capacity to implement climate mitigation and adaptation measures is lacking. From March-May of 2022, a free, live-virtual, evidence and competency based 10-week climate and health course targeted toward health risks in the Caribbean was deployed to: 1) increase communication about climate and health 2) equip health professionals with knowledge and skills that could be readily incorporated into practice, and 3) engage health professionals with climate and health initiatives within their communities. Participants in this course came from 37 countries, 10 different health-related fields, and five different general places of work. Longitudinal surveys revealed significant changes in health professional communication, engagement and application of climate and health knowledge and skills. Live-virtual, evidence and competency-based courses, regional-specific courses have the potential to change health professional behaviors towards addressing climate impacts on health.